PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN SELF EFFICACY SISWA SMK SENTOSA BUAY MADANG - Usmiati, Anggun; Syahbana, Ali; Septiati, Ety (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study is to determine the effect of learning model probing prompting to the ability of mathematical and self-efficacy of students of class XI in SMK SENTOSA Buay Madang. The treatment variable in this research is the learning model of Probing Prompting, dependent variable is the ability of creative thinking and self efficacy of the students. The population in this study is the entire class XI in SMK SENTOSA Buay Madang. The sample in this research is taken by clauster random sampling technique and the selected classes are class XI.1 and XI.3 in SMK SENTOSA Buay Madang. Research is an experimental research with design used in this research is Posttest Only Control Design. Data collection techniques used in this study include tests and questionnaires. Data analysis technique used is Independent Test Samples T-Test. Based on the result of data analysis, it can be concluded that: (1) There is influence of learning model of probing prompting to students' mathematical creative thinking ability. (2) There is influence of learning model of probing prompting to student self efficacy.